Consequence Analysis of LPG-Related Hazards: Ensuring Safe Transitions to Cleaner Energy - Carolina Ardila-Suarez; Jean-Paul Lacoursière; Gervais Soucy; Bruna Rego de Vasconcelos (Fuels, 2025)
Countries worldwide are focused on the objective of zero emissions by 2050. However, the accelerated implementation of clean technologies has had some drawbacks, remarkably those related to safety issues. Liquefied petroleum gas (LPG) emerges as a transition fuel in this context, considering the following two aspects. First, LPG is a fuel that has environmental advantages compared to other fossil fuels, so the extension of coverage as a replacement fuel is a key factor. Second, LPG has a well-developed storage and transportation infrastructure that can be used, sometimes without modifications, for clean fuels, helping their implementation. Therefore, the safety analysis and the study of the consequences related to the hazards of LPG is a current subject that contributes, through all the tools reviewed in this article, to not only reduce the risks of this fuel but also to connect with the safety issues of clean fuels. This review article provides a comprehensive overview through consequence modeling tools, highlighting computational fluid dynamics (CFD) and machine learning to pave the way for the full implementation of clean fuels that will power the future of humanity.